Portfolio business to self-financing of research institution (Case study: Research Institute for Tea and Cinchona) - Srihadiyati Ayu Bestari; M Firdaus; Rohayati Suprihatini; Trias Andati (Jurnal Penelitian Teh dan Kina, 2016)
Case of business portfolio for self financing of  Indonesia Research Institute for Tea and Cinchona is very interesting to study. In general, the research institute of tea in tea producing countries in the world receive financing from the funds cess or levy or Government Budget. In PPTK, is a very rare case because the status of PPTK is a corporate. The unit of research and development as a cost center to produce innovations to increase the competitiveness of national commodity tea as well as Cinchona, should be financed from the portfolio business unit. Therefore, portfolio business strategies are needed in order to play optimally the role of  PPTK accordance with its mandate. The method used to determine the position of corporate is SWOT analysis especially  method to the value of  IFE and EFE. Furthermore, to determine the position and strategize potfolio business units use Boston Consulting Group (BCG) matrix. The results showed that the value of its IFE and EFE (-0.14; 0.11) is in quadrant II that  position of stability/rationalization, which led to the Selective Maintenance Strategy. BCG matrix of the mapping results, the majority of the business portfolio in PPTK be in the Quetion Mark. One business unit shoul be divested is Stevia estate due to its position of the Dog business group. Meanwhile, the business unit of  Cash Cow group are unit of garden and black tea factory and tea experiment garden of Simalungun. In order to better self financing of PPTK, several business units in the group of Question Mark with specific strategies should be push to move into the star groups, namely (1) unit of superior plant material production of tea and cinchona; (2) unit of garden and green tea factory; (3) laboratory services and expertise; and (4) unit of production of white tea and tea packaging.